2014
DOI: 10.1007/s12199-014-0412-8
|View full text |Cite
|
Sign up to set email alerts
|

Skin cancer preventative behaviors in state park workers: a pilot study

Abstract: Based on available evidence, a need exists to develop individual and worksite programs and interventions to increase skin cancer prevention behaviors among this occupational group. This data could serve as a baseline to monitor and evaluate the efficacy of these interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 35 publications
(46 reference statements)
2
24
0
1
Order By: Relevance
“…As barriers to the use of sun protection measures, outdoor workers mentioned discomfort with wearing long‐sleeved clothing often due to heat, forgetfulness and inconveniences caused by wearing wide‐brimmed hats while working …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As barriers to the use of sun protection measures, outdoor workers mentioned discomfort with wearing long‐sleeved clothing often due to heat, forgetfulness and inconveniences caused by wearing wide‐brimmed hats while working …”
Section: Resultsmentioning
confidence: 99%
“…A range of 21–88% of outdoor workers perceived their skin cancer risk above average . Eighty‐seven per cent of US workers stated skin cancer as a serious disease, and 43% believed they would develop skin cancer during their lifetime …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An assessment of sun protection beliefs and behaviors among state park workers found that while the vast majority of the workers (87.4 %) believed that skin cancer is a serious disease, a minority (35.6 %) believed their risk as outdoor workers was higher than average, and a lower proportion was highly confident they could wear a wide-brimmed hat (21.8 %) and sunscreen (20.7 %) while in the sun [27]. These results highlight the need to identify individuals who endorse health promotion beliefs/condemn risk behaviors (and also individuals who endorse sun exposure/ignore sun protection messages).…”
Section: Resultsmentioning
confidence: 99%
“…The variables included in cluster identification procedures were standardized within sample and subsamples (halves) to z scores. Cluster analysis has been used in previous research as a tool to assess cancer prevention outcomes [2427]. …”
Section: Methodsmentioning
confidence: 99%